Application of the Justice Principle for Debtors in Mortgage Rights Auctions and Releases - Yahya, Septian Risaldi; Al Ismariy, Muhammad Nur Karim; Wijayanti, Siti Nur; Sufa, Shaine Veila; Ahmad, Ridho Sa'dillah (Damhil Law Journal, 2024)
Banks, as essential financial institutions, play a critical role in facilitating businesses by providing loans secured with collateral, such as mortgage rights or land certificates. Auctions of collateral encumbered with mortgage rights often face challenges stemming from injustices perpetrated by creditors or debtors. This study aims to explore legal remedies available to debtors when the limit value is set below fair market value and to assess how the principles of justice are applied in mortgage collateral auctions. By analyzing the application of justice principles, procedural frameworks, and legal remedies, this research provides insights into improving auction processes and safeguarding debtor rights. Clear and equitable methods for setting limit values, combined with effective dispute resolution mechanisms, are essential for fostering a fairer and more transparent auction system. This research employs a normative legal methodology, utilizing primary data from webinars and seminars related to mortgage collateral auctions, particularly those organized by KPKNL, and secondary data from legal documents such as the Civil Code, Mortgage Rights Law, PMK on Auction Implementation Guidelines, and Indonesian Valuation Standards. The study underscores the critical importance of procedural justice in mortgage collateral auctions, highlighting the need for reforms in determining limit values. While existing procedures provide a legal foundation, the presence of regulatory gaps necessitates further attention to ensure auctions align with principles of justice and do not disadvantage debtors. Revising regulations and adopting improved practices will support the implementation of fairer and more efficient auctions.